Qualidade de vida no trabalho sob a perspectiva de professores de ensino superior - Rohde, Caroline Lúcia Cantarelli (2012)
Graduate end postgraduate Institutions have felt the transformations that have been happening all over the world, and this has influenced the quality of professors work life. Based on this fact, this work aimed to: (i) comprehend how the quality of work life is perceived by professors in graduate and postgraduate programs in the fields of Social and Human Sciences of a Federal University in a country town of the South Region of Brazil; (ii) understand how the new employment configurations can influence professors life quality; (iii) learn the meaning attributed by professors to the quality of work life and (iv) identify aspects of professors QWL and relate them to the conditions of their professional activity. This work consisted of an empirical, exploratory and descriptive study with a qualitative approach. Data were obtained by means of a semi- structured interview, and the technique of content analysis was used for analyzing the data. Ten professors participated in the research: five taught undergraduates programs and the other 5 also worked in the postgraduate ones. All of them hold a Doctoral Degree and have an exclusive dedication work regime at the University. Data were collected in the months of April, May and June 2011. As a result of the study, two papers were written. In the first article entitled work life quality of professors in graduate and postgraduate programs , a non-systemic literature review of the comprehension of the life quality of professors who work in graduate and postgraduate programs was undertaken. The study aimed to present the main elements which are part of the notion of quality of work life emphasizing how professors dealt with this issue especially in graduate and postgraduate programs. In the second article, the empirical research called quality of working life from the perspective of professors of graduate end postgraduate programs of a Public University , three categories were described: new demands and greater requirements; meanings of the quality of working life, and aspects mentioned about professors QWL which were discussed based on related theories. The results of the first study made it clear that several elements are essential for the quality of work life of professionals in graduate and postgraduate programs such as the individual pathway, the organizational aspects of the institutions and the social environment in which these workers are incorporated. Therefore the set of these elements will influence the way the teachers perceive their professional activity and this will reflect into the quality of life at work as well as into the quality of their performance in the education process of future professionals. In the second article, it became evident that regardless of whether the teachers were working or not in postgraduate programs, they have the same perception about the increase of workload, which happens after the qualification process, a requirement they need to fulfill. The teachers feel they have to work harder to fulfill the requirements in the postgraduate programs, and this seems to unleash a negative reaction once they recognize that teaching is being directed to other purposes, that is, to fulfill the requirements of publications to achieve the score established by the Ministry of Education. Moreover, it is necessary a discussion about the aspects that comprehend the quality of work life, as a way of fostering an awareness on professors and Institutions about the care they should take with the health of their professors and provide a better work environment to them.